Hybrid Propulsion System (PV / Gasoline) For Small Fishing Vessels - Sultoni, Arif Indro; Ali, M. Marhaendra; Aji, Zaenal Panutup (Department of Naval Architecture - Diponegoro University, 2020)
The mechanism of hybrid (PV+gasoline) for fishing vessel propulsion was aimed to reduce fuel consumption.Â The background of this research is lots of vessels not going for fishing because of a lack of fuel. With the hybrid mechanism, the fishing vessels could less fuel consumption without decreases its performance (torsion, power durability, and velocity) when cruising. In this paper, a parallel hybrid (PV/gasoline) is proposed. The gasoline generator will deliver power to DC motor if PV energy that stored to the battery not enough as the requirement of propeller propulsion. Hybrid design for a 3-ton overall weight of fishing vessel was designed with eight-unit solar panels @200 WP arranged as four string-2 series. Li-Ion battery pack with 4.5 KWH of capacity was used as energy storage. The simulation shows that the hybrid scheme can preserve the vessel speed at 16 Km per hour with time duration in 12 hours 46 minutes and needs 4 hours 10 minutes for full battery charging by a gasoline generator.